Soviet federalism from below: the Soviet Republics of Odessa and the Russian Far East, 1917-1918 - Penter, Tanja; Sablin, Ivan (Journal of Eurasian studies, 2020)
In early 1918, the Bolshevik-dominated Third Congress of Soviets declared the formation of a new composite polity—the Soviet Russian Republic. The congress’s resolutions, however, simultaneously proclaimed a federation of national republics and a federation of soviets. The latter seemed to recognize regionalism and localism as organizing principles on par with nationalism and to legitimize the self-proclaimed Soviet republics across the former Russian Empire. The current article compared two such non-national Soviet republics, those in Odessa and the Russian Far East. The two republics had similar roots in the discourses and practices of the Russian Empire, such as economic and de facto administrative autonomy. They also took similar organizational forms, were run by coalitions, and opposed their own inclusion into larger national and regional formations in Ukraine and Siberia. At the same time, both of the Soviet governments functioned as ad hoc committees and adapted their institutional designs and practices to the concrete—and very different—social and international conditions in the two peripheries. The focus of the Odessa and Far Eastern authorities on specific problems and their embeddedness in the peculiar contexts reflected the very idea of federalism as governance based on decentralization and nuance but contradicted the party-based centralization and the exclusivity of the ethno-national federalism in the consolidated Soviet state.